MSOE Underwater Robotics: The Mosquito - Ahern, Allison Marie (Proceedings of the Wisconsin Space Conference, 2017)
The MSOE ROV team is a fourth year student organization at the Milwaukee School of Engineering that competed at an international ROV competition that took place at the NASA Neutral Buoyancy Lab. The goal was to create an ROV that could complete tasks that simulate bringing the ROV into space and exploring one of Jupiterâ€™s moons, Europa. Named Mosquito for its appearance, the ROV was designed specifically to be compact and light to allow for easy transportation to remote parts of the world. The system is broken down into subsystems that could easily interface and synergize with each other to accomplish all of the needed tasks related to the mission to Europa, including collecting cube sats and oil samples, studying coral, and converting oil rigs to reefs, all while diving deep.Â 